Technical Cooperation – Description Of Action: Submitted by the Inter-American Institute for Cooperation on Agriculture (IICA) to The Cropper Foundation - IICA, Port-of-Spain (Trinidad y Tobago) (2021)
With COVID19 the need to reduce vulnerability to import and global food chain disruption, has placed greater focus on expanding domestic food production and marketing and building resilience in agriculture value chains that is inclusive of micro and small operators - farmers and agro-processors. TCF's resources will support acquisition of professional services tailored to the specific needs of the target beneficiaries already involved in farming and food marketing and distribution to enhance their operational efficiency and expand their presence in the domestic market. IICA will leverage its technical expertise and capacity to broker relationships to add value to the efforts of existing actors and provide materials and supplies needed to properly implement the activities